A review of electrodeposition techniques and variables for production of nickel-cobalt / alumina (Ni-Co/Al2O3) composite coatings - Nik Yusoff, N.H. (Science and Technology Research Institute for Defence, 2015)
This paper provides a review of the electrodeposition process that is used to produce nickel-cobalt / alumina (Ni-Co/Al2O3) composite coatings. The electrodeposition techniques, consisting of direct current, pulse current and pulse reverse current, sediment electrodeposition, and CO2 bath, are described. The effects of electrodeposition variables, including applied current density, deposition time, particle concentration and use of surfactants, are also explained. The paper then discusses the limitations of previous studies, such as lack of focus on the effectiveness of this coating in corrosive and erosive environments, and the effects of alumina particles on coating microstructures. It also suggests longer exposure to corrosive media for more significant corrosion study. Further research needs to be conducted in order to improve the corrosion and erosion resistance of Ni-Co/Al2O3 in harsh environments, such as marine conditions.